Best practice in primary care pathology: review 11. Issue 4 (26th October 2007) - Smellie, W S A; Vanderpump, M P J; Fraser, W D; Bowley, R; Shaw, N
Abstract : This eleventh best practice review examines two series of common primary care questions in laboratory medicine: (i) thyroid testing, and (ii) hypercalcaemia and hypocalcaemia. The review is presented in the same question–answer format as in the previous reviews. These questions and answers deal with common situations in men and non-pregnant women. The recommendations represent a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence-based medicine reviews, supplemented by Medline Embase searches to identify relevant primary research documents. In the case of the thyroid series, the recommendations are drawn from the 2006 guidelines published by the Association for Clinical Biochemistry, the British Thyroid Association and the British Thyroid Foundation. They are not standards but form a guide to be set in the clinical context. Most are consensus rather than evidence based. They will be updated periodically to take account of new information.